A short ncRNA modulates gene expression and affects stress response and parasite differentiation in Leishmania braziliensis - Quilles, José C.; Espada, Caroline R.; Orsine, Lissur A.; Defina, Tânia A.; Almeida, Letícia; Holetz, Fabíola; Cruz, Angela K. (Frontiers in Cellular and Infection Microbiology, 2025)
The protozoan parasite Leishmania spp. is a causative agent of leishmaniasis, a disease that affects millions of people in more than 80 countries worldwide. Apart from its medical relevance, this organism has a genetic organization that is unique among eukaryotes. Studies of the mechanisms regulating gene expression in Leishmania led us to investigate noncoding RNAs (ncRNAs) as regulatory elements. We previously identified differentially expressed (DE) ncRNAs in Leishmania braziliensis with potential roles in the parasite biology and development. Herein, we present a functional analysis of one such DE ncRNA, the 147-nucleotide-long transcript ncRNA97, which is preferentially expressed in amastigotes, the replicative form within mammalian phagocytes. By RT-qPCR the ncRNA97 was detected in greater quantities in the nucleus under physiological conditions and in the cytoplasm under nutritional stress. Interestingly, the transcript is protected at the 5’ end but is not processed by the canonical trypanosomatid trans-splicing mechanism, according to the RNA circularization assay. ncRNA97 knockout (KO) and addback (AB) transfectants were generated and subjected to phenotypic analysis, which revealed that the lack of ncRNA97 impairs the starvation response and differentiation to the infective form. Comparative transcriptomics of ncRNA97KO and parental cells revealed that transcripts encoding amastigote-specific proteins were affected. This pioneering work demonstrates that ncRNAs contribute to the developmental regulatory mechanisms of Leishmania.